2016
DOI: 10.1016/j.vaccine.2016.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Costs of introducing pneumococcal, rotavirus and a second dose of measles vaccine into the Zambian immunisation programme: Are expansions sustainable?

Abstract: BackgroundIntroduction of new vaccines in low- and lower middle-income countries has accelerated since Gavi, the Vaccine Alliance was established in 2000. This study sought to (i) estimate the costs of introducing pneumococcal conjugate vaccine, rotavirus vaccine and a second dose of measles vaccine in Zambia; and (ii) assess affordability of the new vaccines in relation to Gavi’s co-financing and eligibility policies.MethodsData on ‘one-time’ costs of cold storage expansions, training and social mobilisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Most of the countries, including the 18 countries that did not report on donor funding, have unrealistically low immunization budget allocations per child in the birth cohort, such as US$1.54 in Burundi, US$1.99 in Sierra Leone and 2.96 in Liberia. Since vaccine costs of the ‘standard’ childhood vaccination schedule amounts to at least US$20 per child in the birth cohort, the budget allocations do not align with the amount of funding known to be spent on immunization ( Ahanhanzo et al , 2015 ; Griffiths et al , 2016 ; Geng et al , 2017 ). Explanations for the relatively low budget allocations include omission of donor funding, exclusion of ‘shared costs’, which may be reported elsewhere in the budget, and inaccurate budget predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the countries, including the 18 countries that did not report on donor funding, have unrealistically low immunization budget allocations per child in the birth cohort, such as US$1.54 in Burundi, US$1.99 in Sierra Leone and 2.96 in Liberia. Since vaccine costs of the ‘standard’ childhood vaccination schedule amounts to at least US$20 per child in the birth cohort, the budget allocations do not align with the amount of funding known to be spent on immunization ( Ahanhanzo et al , 2015 ; Griffiths et al , 2016 ; Geng et al , 2017 ). Explanations for the relatively low budget allocations include omission of donor funding, exclusion of ‘shared costs’, which may be reported elsewhere in the budget, and inaccurate budget predictions.…”
Section: Discussionmentioning
confidence: 99%
“…A range of factors may contribute to lower than desirable levels of vaccine introduction. Decision-making processes, economic and financial aspects of NVIs are critical ones and have been extensively described [10][11][12][13][14][15][16][17][18][19][20]. Besides these aspects, implementation and integration of new vaccines bring additional logistical complexity to delivery of existing immunization programs in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…When accounting for averted healthcare-related costs for households, using either vaccine is a costsaving intervention, highlighting the economic burden rotavirus represents for households and the health system in Palestine. Other studies conducted in the EMRO region have also found that rotavirus vaccine introduction is cost-effective or cost-saving compared to no vaccination [14,36,37]. When evaluating the switch, ROTAVAC presents an economic advantage over ROTARIX and shifting from ROTARIX to ROTAVAC was a cost-saving option from both the health system and societal perspectives.…”
Section: Discussionmentioning
confidence: 95%